BVI photometry and integrated spectroscopy of the very young open clusters Ruprecht 119, NGC 6318 and BH 245 - Piatti, Andres Eduardo (2000)
We present CCD BVI observations obtained for stars in the fields of the unstudied or poorly studied open clusters Ruprecht 119, NGC 6318, and BH 245 projected close to the direction towards the Galactic centre. We measured V magnitude and B-V and V-I colours for about 600 stars reaching down to V ~ 19 mag. From the analysis of the colour magnitude diagrams, we confirmed the physical reality of the clusters and derived their reddening, distance and age for the first time. In addition, we obtained flux-calibrated integrated spectra in the range 3500-9200 Å for the cluster sample. Using the equivalent widths of the Balmer lines and comparing the cluster spectra with template spectra we derive both foreground reddening and age. The photometric and spectroscopic results reveal that the three studied objects are very young open clusters with ages ranging between 10 and 15 Myr, which have already undergone the HII region evolutionary phase and are dominated by the upper MS stars. The clusters, located between 1.1 kpc and 3.3 kpc from the Sun, are affected by different amounts of interstellar visual absorption (2.4 <= A_v <= 7.0). In particular, BH 245 turned out to be a highly reddened open cluster located at a distance of scarcely 1.1 kpc.